Bilateral sagittal spilt mandibular ramus osteotomy: The influence of stripping the medial pterygoid muscle on proximal segment control for mandibular advancement procedures. - Geldenhuys, Barry (My University, 2014)
One of the goals during surgical repositioning of the mandible is to ensure a correct condyle-fossa relationship and to maintain the position of the proximal segment at the time of placement of rigid fixation. During setback procedures, accurate control of the proximal segment is influenced by the medial pterygoid muscle and stylomandibular ligament. These structures are therefore stripped from the medial surface of the mandibular angle during surgery. The aim of this study was to investigate the influence of the muscle attachment on proximal segment control in mandibular advancement surgery. Clockwise or counterclockwise rotations of the proximal segment during surgery of two groups of patients were compared. In one group, the medial pterygoid muscle was stripped during surgery while in the other group the medial pterygoid muscle was left attached. The second group formed part of the historical development phase of the surgical technique for mandibular advancement procedures.
Department of Maxillofacial and Oral Surgery, 2013
Keywords: Mandible--surgery